Project-induced displacement and resettlement: from impoverishment risks to an opportunity for development?. Issue 1 (2nd January 2017) - Vanclay, Frank
Abstract: While the World Bank safeguard policies and International Finance Corporation Performance Standards specify the requirements to be observed when project-induced displacement and resettlement occurs, these international standards are not always followed. Governments often invoke the power of eminent domain and implement expropriation procedures instead of building support for a public or private project by negotiating with project-affected peoples. Evaluations of projects reveal that people are usually made worse off by being resettled. This paper provides a general introduction to the topic of project-induced displacement and resettlement, raising the key issues facing resettlement practice: under what conditions should projects and associated resettlements proceed; what constitutes appropriate compensation; can livelihoods be restored or improved; what is the role of benefit sharing and shared value; and how resettlement practice can be improved. Although there is ongoing improvement in the discourse and practice of project-induced resettlement, being resettled is still likely to be an impoverishment risk and have an emotional toll. Hopefully, however, under the right conditions, resettlement has the potential to be an opportunity for development.